EAR CANKER IN A RABBIT – A CASE REPORT - S. Ramya; N.V. Rajesh; E. Madhesh; V. Vijayanand; R.B. Vishnurahav; M. Balagangatharathilagar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A three-month-old female New Zealand White Rabbit, weighing about 1.4 kg was brought to the Veterinary Clinical Complex, Veterinary College and Research Institute, Tirunelveli with ahistory of intense pruritis and alopecia all over the body. Clinical observation revealed crusty lesions on the nose,ear margin and toes. Microscopic examination of the deep skin scraping revealed the presence of Psoroptes cuniculi mite. The rabbit was treated with an injection Ivermectin @ 0.4 mg/kg sub-cutaneous and an injection of Chlorpheniramine maleate @ 0.4 mg/kg intramuscular and further advised the owner to give HITEK® oral solution (Ivermectin) @ 0.4 mg/kg PO once a week and Benzyl benzoate I.P. solution topically daily for a continuous period of one month along with multivitamin supplementation (Multistar pet®) @ 2 ml PO BID. The rabbit recovered successfully without any drug side effects (Tandem usage of ivermectin and Benzyl Benzoate).